Silicone gel sheeting for treating hypertrophic scars - Jiang, Qingling (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness of silicone gel sheeting in the treatment of hypertrophic scars compared with standard care or other therapies.